2013
DOI: 10.1021/ja4026424
|View full text |Cite
|
Sign up to set email alerts
|

Divergence between Organometallic and Single-Electron-Transfer Mechanisms in Copper(II)-Mediated Aerobic C–H Oxidation

Abstract: Copper(II)-mediated C-H oxidation is the subject of extensive interest in synthetic chemistry, but the mechanisms of many of these reactions are poorly understood. Here, we observe different products from Cu(II)-mediated oxidation of N-(8-quinolinyl)benzamide, depending on the reaction conditions. Under basic conditions, the benzamide group undergoes directed C-H methoxylation or chlorination. Under acidic conditions, the quinoline group undergoes nondirected chlorination. Experimental and computational mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
270
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(284 citation statements)
references
References 69 publications
10
270
2
2
Order By: Relevance
“…[17] Stahl and co-workers reported the copper-mediated methoxylation of N-(8-quinolinyl)benzamide by employing methanol as the solvent. [18] Later on, Niu inde-pendently reported a copper-mediated direct aryloxylation of benzamides assisted by an N,O-bidentate directing group. [19] Very recently, You and co-workers reported a copper-mediated, tandem oxidative alkyn-A C H T U N G T R E N N U N G ylation and annulation of arenes with terminal alkynes by taking advantage of the bidentate-chelation assistance of an 8-aminoquinoline residue [20] while Yu and co-workers discovered the copper-mediated ortho C À H alkynylation and trifluoromethylation of arenes by using an amide-oxazoline directing group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Stahl and co-workers reported the copper-mediated methoxylation of N-(8-quinolinyl)benzamide by employing methanol as the solvent. [18] Later on, Niu inde-pendently reported a copper-mediated direct aryloxylation of benzamides assisted by an N,O-bidentate directing group. [19] Very recently, You and co-workers reported a copper-mediated, tandem oxidative alkyn-A C H T U N G T R E N N U N G ylation and annulation of arenes with terminal alkynes by taking advantage of the bidentate-chelation assistance of an 8-aminoquinoline residue [20] while Yu and co-workers discovered the copper-mediated ortho C À H alkynylation and trifluoromethylation of arenes by using an amide-oxazoline directing group.…”
mentioning
confidence: 99%
“…Extensive screening studies showed that the efficiency of the reaction could be significantly affected by the choice of the base used and K 2 HPO 4 was determined to be the best base for this reaction (Table 1, entries 2-7). It is important to note that the selectivity [15][16][17][18]. When the reaction was conducted in DMF, much to our surprise, the selectivity of mononitrated product 2a vs. dinitrated product 3a was reversed and they are isolated in a 1:2 ratio with a 46% combined yield (Table 1, entry 19).…”
mentioning
confidence: 99%
“…11 In fact, the picolinamide group (COPy) has proven to be highly efficient in promoting a variety of C(sp 2 )-H and C(sp 3 )-H bond functionalization reactions, 5e,12 whereas derivatization at the pyridine ring has been seldom reported. 13 This gap stimulated us to develop a practical method for the Rh III -catalyzed olefination/annulation of picolinamides. Remarkably, the resulting pyrrolo [3,4-b]pyridines can be considered as conformationally constrained nicotinoids, thereby becoming attractive candidates for selective nicotinic acetylcholine receptor ligands, or dipeptide mimics.…”
mentioning
confidence: 99%
“…of Cu(OAc) 2 (Scheme 11). [20] In order to gain furtheri nsight into these newt ransformations, they have performed various fundamental mechanistics tudies including deuterium-labelling experiments,H ammett studies as well as computational studies on Cu(II)-mediated methoxylation of 8-aminoquinoline benzamide.A ll these studies indicated that the process indeed goes through aCu(II)-mediated C À Hactivation.…”
Section: C à Ob Ond Formationmentioning
confidence: 99%